Reaction time as a stochastic process implemented by functional brain networks. Issue 2 (3rd April 2017) - Siettos, Constantinos I.; Smyrnis, Nikolaos
ABSTRACT: Many studies focus on anatomical brain connectivity in an effort to explain the effect of practice on reaction time (RT) that is observed in many cognitive tasks. In this commentary, we suggest that RT reflects a stochastic process that varies in each single repetition of any cognitive task and cannot be attributed only to anatomical properties of the underlying neuronal circuit. Based on recent evidence from Magnetoencephalographic, Electroencephalographic, and fMRI studies, we further propose that the functional properties of key brain areas and their self-organization into functional connectivity networks contribute to the RT and could also explain the effects of training on the distribution of the RT.